IDENTIFYING THE FIFTH SEMESTER STUDENTS’ ABILITY IN PRONOUNCINGTHE ENGLISH VOICELESS PLOSIVE CONSONANTS AT ENGLISH STUDY PROGRAM AT UNIVERSITY OF BATURAJA - Aldo Hilamanando; Neti Lastri; Henny Yulia (Program Studi Pendidikan Bahasa Inggris - Fakultas Keguruan dan Ilmu Pendidikan - Universitas Baturaja, 2021)
Pronunciation is as an aspect of the language has a great influence onour successful communication but it is still ignored by teachers, who rather pay attention to teaching grammar as they feel more important. The objective of the study isto find out ability in pronouning the English voiceless plosive consonants [P], [T], [K] at English Study Program at University Of Baturaja.The population of this research wasthe students of English Education Study Program at Baturaja University. The researcher took only in semester V because students have been learnt speaking I,II, III dan pronounciation courses. Based on the finding, it could be concluded as follow; the frequency students’ score criteria described there were 4 students (18,19%) who gained score 80-100 in level very good, 8students (36,36%) who gained score 66-79 in level good, 7 students (31,81%) who gained score 56-65 in level enough, 3students (13,64%) who gained score 46-55 in level low and no students got score < 45 in level fail. Based on calculation above, the mean score 65,15 showed that in identifying the Fifth Semester Students’ ability in Pronouncing the English Voiceless Plosive Consonants at English Study Program at University of Baturaja was good.